A study on factors affecting customers'decision to eat or not to eat in eat-all-you-can restaurants - Eguilos, Remi Arden P.; Jorolan, Noel H.; Leuterio, Leimonel Charilou G.; Morales, James L.; Sorongon, Genelyn R. (2005)
Eat all you can restaurants are startig to grow in the food service industry. It has flourished and has become rampant in different places in Philippines, In Iloilo City, the existence of eat all you can restaurant can be observed. This study aims to determine the factors that affect the decision of a customer to eat or not to eat in an eat all you can restaurant as well as the effects of change in the level of income on these factors. This study focused on eat all you can restaurants established in Iloilo City including hotels and other restaurants offering eat all you can services. The respondents involved included both the students and non-students within Iloilo City. This study will be beneficial to eat all you can restaurants in improving their operations. In addition, this study can help understand the behavior and attitude of people towards eat all you can restaurants. The researchers have identified several factors that affect a customer's decision. Primarily, it includes the variety of food served, price, ambiance, customer service, location or accessibility and advertisements. These identified factors indeed affect their decision in availing eat-all-you can restaurant services. Variety of food is the greatest factor that they consider that influence their decision as supported by the Philippine culture that Filipinos are used to prepared variety of food in their banquets. Native foods are among the food preferred by Ilonggos. Respondents prefer to avail eat-all-you-can restaurant services who offered food with prices ranging from p99-105 and prefer restaurant with music, air-conditioned, and with unique restaurant setting. In addition the respondents found out that customers prefer restaurant offering fast service, and located near school or their working place. Their decision is also affected by their kind of advertisement the restaurant is extending. Television advertisement greatly affects their decision. The researchers also found out that with the change in the level of income, order of priority of factors being considered also changes. When level of income increase, the first factor that they will consider is still the variety of food, while price is the great factor that they will consider when their income decreases. with regard to respondents who do not avail f eat-all-you-can-restaurant services, the greatest factor that hinders them from availing of such services is the price of food offered. The researchers also found out that increase in the levels of their income will affect their decision.They consider customer services as the primary factor that they will consider when their income increases. After thorough analysis of findings gathered, the researchers conclude that a customer's choice of availing services in an eat-all-you-can restaurant is influenced by factors such as variety of food, prices, customer service, ambiance, location or accessibility and advertisements. Among these factors, variety of food is the primary factor that they consider. On the other hand, the price is the primary hindrance why customer does not eat in eat-all-you-can restaurant. However, the increase in their level of income will change the factor that they consider as their primary hindrance, which is now the poor customer service. In order for an eat all you can restaurant to be competitive or earn above-average returns, they should consider the factors identified by the researchers. They should also identify their target market and consider the level of income and expenditure of such market to create customer satisfaction and maintain their market position. The researchers recommended that the study be expanded to a greater number of samples as well as consider respondents fro other places outside Iloilo City. Through this, additional factors that might be considered by a customer in its decision to eat or not to eat in eat-all-you-can restaurant may be obtained.
Research Paper (BA 200-Business Research). -- Iloilo City : UPV-CM, March 21, 2005.